DA'WAH MODERATION (A STUDY OF TGH. SHAFWAN HAKIM'S THOUGHTS ON ISLAMIC MODERATION) - Lalu Ahmad Zaenuri (Universitas Islam Negeri Mataram, 2022)
Understanding religious teachings well is a necessity; this will be achieved if the da'i/muballigh, as the deliverer of the da'wah message, has a good understanding of religious teachings, as done by Tuan Guru Haji (TGH) Shafwan Hakim. The strategic position of a da'i in the eyes of the community makes it very easy to color their thoughts and religious expressions. This study is a qualitative character study that describes moderation in da'wah; it is a study of TGH. Shafwan Hakim's thoughts on preserving Islamic moderation. The thinking of TGH. Shafwan Hakim in presenting da'wah in moderation must start with sense of moderate, da'wah material oriented to the benefit of the ummah, and preachers' understanding of their mad'u, methods, and media.